2020
DOI: 10.9744/jmk.22.1.65-72
|View full text |Cite
|
Sign up to set email alerts
|

Generational Diversity, Personal Attributes and Organizational Commitment Among Employees of Corporate Consultancies

Abstract: The main objective of this paper was to examine relationships of generational diversity, personal attributes (i.e., work values; attitudes and behavior; and interpersonal skills) on organizational commitment among employees of corporate consultancies. The research framework contained four independent variables which were generational diversity, work values, attitude and behavior, and interpersonal skills. Meanwhile the dependent variable was organizational commitment (i.e., affective, continuance and normative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The findings suggest higher levels of commitment when organisations are viewed as reflecting ideals associated with Benevolence and Vision (Verasamy, Majid and Jamaluddin, 2020). The ideals of vision and humanity usually correlate with the forms of pan-cultural values of Benevolence, Universalism and Self-Direction.…”
Section: Independent Variables Personal Valuesmentioning
confidence: 87%
See 4 more Smart Citations
“…The findings suggest higher levels of commitment when organisations are viewed as reflecting ideals associated with Benevolence and Vision (Verasamy, Majid and Jamaluddin, 2020). The ideals of vision and humanity usually correlate with the forms of pan-cultural values of Benevolence, Universalism and Self-Direction.…”
Section: Independent Variables Personal Valuesmentioning
confidence: 87%
“…However, to the researcher knowledge, no study has found the link between personal value and continuance commitment. Meyer and Allen (1997); Khalid (2020); Kumasey, Bawole and Hossain (2017) and Verasamy, Majid and Jamaluddin (2020) argued that one can achieve a better understanding of an employee's relationship with an organization when all three forms of commitment are considered together. Based on this contention, current study subscribe to the Three Commitments (Affective, Continuance and Normative) have to be studied together to better understand Organizational Commitment among foreign workers.…”
Section: )mentioning
confidence: 99%
See 3 more Smart Citations